Some Best Practices for Inclusive Environments in Higher Education - Csovcsics, Erika (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Book: Berg, G. A., & Venis, L. (2020). Accessibility and Diversity in the 21st Century University (pp. 1-300). Hershey, PA: IGI Global. doi:10.4018/978-1-7998-2783-2